Antifungal Activity of Aerial Parts of Cenchrus pennisetiformis Against Fusarium oxysporum f. sp. lycopersici - KHURSHID,S. (2018)
ABSTRACT: Antifungal potential of aerial parts of an allelopathic grass Cenchrus pennisetiformis (Hochst. & Steud.) Wipff. was evaluated against Fusarium oxysporum f. sp. lycopersici Snyder & Hansen, a fungal pathogen causing wilt disease in tomato (Solanum lycopersicum L.). Different concentrations (1% to 6%) of methanolic leaf, stem and inflorescence extract of the grass significantly reduced fungal biomass by 40-88%, 13-89%, and 26-76%, respectively. Methanolic shoot (leaf + stem) extract was fractionated using four organic solvents viz. n-hexane, chloroform, ethyl acetate and n-butanol. All the sub-fractions of methanolic shoot extract showed remarkable antifungal potential to variable extents. Different concentrations (1.56-200 mg mL-1) of ethyl acetate sub-fraction exhibited the best antifungal activity resulting in 49-100% suppression in the fungal biomass. GC-MS analysis of ethyl acetate sub-fraction showed the presence of 10 compounds. Phenol, 2,4-bis{1,1-dimethlethyl}- was the major compound (30.99%) followed by hexadecanoic acid, ethyl-ester (21.72%), benzofuran 2,3-dihydro (10.65%), 1-propanol-2-2-hydroxypropxy (10.60%) and 1-eicosene (8.32%).